Induction and secretion of elastinolytic and proteolytic activity in cultures of Paracoccidioides brasiliensis - Voltan, A. R. [UNESP]; Donofrio, F. [UNESP]; Miranda, E. T. [UNESP]; Moraes, R. A. [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (My University, 2008)
P. brasiliensis parasitizes various human tissues and proteinases exported by this fungus may allow it to metabolize and invade host tissues. The influence of the culture medium on the production of proteinases by P. brasiliensis isolates was studied and the export of these enzymes was followed as a function of culture time. The fungus was grown in neopeptone, BSA, elastin or collagen medium. The culture medium was assayed for azocollytic, elastinolytic and caseinolytic activity. Proteolytic activity was also analysed by electrophoresis of the culture medium on gelatin and casein substrate gels. P. brasiliensis expressed relatively high levels of azocoll, elastin and casein degrading activity in all types of medium, except in neopeptone medium. Generally, expression of azocollytic activity peaked during the third week of culture and caseinolytic activity during the fourth week of culture. Azocollytic activity was highest at pH 4.0 and caseinolytic activity at pH 8.0. Elastinolytic activity was also highest at pH 8.0. This activity, as well as the others, may provide the fungus with a source of carbon and nitrogen and may also be responsible for the invasion of host tissues, such as pulmonary elastic fiber, by P. brasiliensis.
Keywords: Collagenolytic activity; Elastinolytic activity; Paracoccidioides brasiliensis; Paracoccidioidomycosis; Proteolytic activity; carbon; casein; elastin; gelatin; nitrogen; culture medium; elastic fiber; elastolysis; fungus culture; fungus growth; fungus isolation; nonhuman; pH; polyacrylamide gel electrophoresis; protein degradation; protein induction; protein secretion; protein synthesis